Impact of Stem Cells in Craniofacial Regenerative Medicine - Sanchez, Pedro A.; Zhao, Hu; Abdelhamid, Alaa I.; Warburton, David (Frontiers in Physiology, 2012)
Interest regarding stem cell based therapies for the treatment of congenital or acquired craniofacial deformities is rapidly growing. Craniofacial problems such as periodontal disease, cleft lip and palate, ear microtia, craniofacial microsomia and head and neck cancers are not only common but also some of the most burdensome surgical problems worldwide. Treatments often require a multi-staged multidisciplinary team approach. Current surgical therapies attempt to reduce the morbidity and social/emotional impact, yet outcomes can still be unpredictable and unsatisfactory. The concept of harvesting stem cells with expansion, differentiation, seeding onto a scaffold and re-transplanting them is likely to become a clinical reality. In this review, we will summarize the likely translational applications of stem cell therapies in tissue regeneration for craniofacial defects.